A história em quadrinhos enquanto representação política: Capitão América e Caveira Vermelha (1941/1999) - Melo, Shesmman Fernandes Barros de (2012)
The present paper aims to make an analysis on the comic books to understand the social and political representations in the six decades of publication of the character Captain America, as well as the importance of Red Skull to the mythology of this character. To do so it is necessarythe contextualization of the comic book as a means of mass communication and, therefore, susceptible to be used as an instrument of both political and social representations of a determined period. In this context, Captain America's stories become a highly valued study subject, to analyze the chronological evolution of this character is, also, to analyze the historical, political and ideological trajectory of the United States between the 1940's and the 1990's. We realized that the question would not be answered that simply and to achieve its completion we searched various areas for the means to decipher it. With the theory developed by Joseph Campbell named 'Hero's Journey' we understand how the heroic figures of the comic books characters, structuring in the collective imaginary to achieve the representation towards the public. However, it offers only a partial answer; the complement necessary to the full understanding of the problem was found in the conflict between both characters. Therefore, it is possible to state that the fictional universe of Captain America survived sixty years of publishing thanks to the modifications in which it brought represented on its pages the fears and wishes of the American Society, and for this purpose Red Skull played a core role.